THE RESPONSIBILITY OF PT. PEGADAIAN SYARIAH BANDA ACEH FOR THE LOSS OF COLLATERAL OBJECT : Study of the Financial Services Authority Regulation No. 31 of 2016 on Pawnshop Business - Marwah Adi Halim, Zahratun; Mawar, Sitti; Ramli, Misran (Program Studi Hukum Ekonomi Syariah Fakultas Syariah dan Hukum UIN Ar-Raniry, 2024)
PT. Pegadaian Syariah is an alternative financing institution that provides loans based on the law of pawn, which requires the submission of movable goods as collateral from customers to PT. Pegadaian Syariah. The focus of this study is on the form of responsibility and the explanation of how PT. Pegadaian Syariah Banda Aceh resolves compensation for the loss of the pawned objects. To answer this research question, the method used is a normative juridical approach. Normative juridical is a system for selecting legal regulations, doctrines applied to provide answers to legal cases, and using a statute-based approach. The findings of this study conclude that if a case of damage or loss of collateral occurs during the pawn process, PT. Pegadaian Syariah is responsible for the damaged or lost collateral. In providing compensation, PT. Pegadaian Syariah must adhere to the provisions set out in the Pawnshop Work Procedures Handbook, which governs how compensation should be provided if the collateral is lost